Performance of hilly and naked neck hilly chicken at Naikhongchari of Bangladesh - Alam, MA; Khatun, R; Hasan, MT; Rakib, MRH; Hossain, MA (Bangladesh Journal of Animal Science, 2022)
A study was conducted to evaluate the production and hatching performances of hilly chickens and naked neck (NN) hilly chickens at the hilly areas of Naikhongchari regional station research farm of Bangladesh Livestock Research Institute (BLRI). The experimental chickens were reared in an open-sided poultry house under an intensive management system for a period of 18 month. The birds were allowed to take feed and clean drinking water ad libitum. Data on productive and reproductive performances of hilly and NN hilly chickens were recorded regularly. Result revealed that no significant (P>0.05) difference on body weight of day old, 2nd weeks and 4th weeks of age but significantly (P<0.05) differ on 6th to 12th weeks of age on hilly and NN hilly chicken. Result also showed that average feed intake and mortality percentage at day old to 12th weeks of age were significantly (P<0.05) differ among hilly and NN hilly chicken. It was found that no significant (P>0.05) difference of egg weight and chick weight between hilly and NN hilly chicken but significantly (P<0.05) differed in hatchability percentage. On the other hand, result exhibited that average body weight (ABW) of cock and hen, feed intake and mortality were significantly (P<0.05) differed among hilly and NN hilly chicken. Hen days egg production was significantly (P<0.05) differed between hilly and NN hilly chicken but no significant (P>0.05) difference of average total egg weight and age at first egg. These findings imply that Hilly chicken performance was better than NN hilly chicken in terms of body weight (BW), age at first egg (AFE) and egg production. Both hilly (feathered) and NN hilly chickens need to be conserved and improved further through selective breeding and a better management system. Bangladesh Journal of Animal Science 51 (3): 133-137, 2022